2004
DOI: 10.1074/jbc.m405247200
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase Activity of Fibroblast Growth Factor Receptor 3 with Activation Loop Mutations Affects Receptor Trafficking and Signaling

Abstract: Amino acid substitutions at the Lys-650 codon within the activation loop kinase domain of fibroblast growth factor receptor 3 (FGFR3) result in graded constitutive phosphorylation of the receptor. Accordingly, the Lys-650 mutants are associated with dwarfisms with graded clinical severity. To assess the importance of the phosphorylation level on FGFR3 maturation along the secretory pathway, hemagglutinin A-tagged derivatives were studied. The highly activated SADDAN (severe achondroplasia with developmental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 27 publications
3
70
0
1
Order By: Relevance
“…Correct glycosylation of the receptor is required for its normal processing to the plasma membrane and occurs both in the endoplasmic reticulum (ER) and the Golgi system. 23,24 Defective glyco- Novel FGFR3 mutations S Heuertz et al has been reported with the K650N mutation causing HCH. 24 Another mutation (N328I) affecting a putative glycosylation site has been reported previously 10 and identified in one of our patients; both mutations were associated with typical HCH phenotype in the affected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct glycosylation of the receptor is required for its normal processing to the plasma membrane and occurs both in the endoplasmic reticulum (ER) and the Golgi system. 23,24 Defective glyco- Novel FGFR3 mutations S Heuertz et al has been reported with the K650N mutation causing HCH. 24 Another mutation (N328I) affecting a putative glycosylation site has been reported previously 10 and identified in one of our patients; both mutations were associated with typical HCH phenotype in the affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Defective glyco- Novel FGFR3 mutations S Heuertz et al has been reported with the K650N mutation causing HCH. 24 Another mutation (N328I) affecting a putative glycosylation site has been reported previously 10 and identified in one of our patients; both mutations were associated with typical HCH phenotype in the affected individuals. Amino acids forming the Ig I loop are poorly conserved among the different members of the FGFR family.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of ligand, the GFP-tagged FGFR3 localized to the cell membrane ( Fig. 3A) (Lievens et al, 2004). Addition of FGF induced internalization of the receptor, as can be seen by its localization in the cytosol in diffused and granular form, and its clustering prominently in the perinuclear region (Fig.…”
Section: Socs1 and Socs3 Bind Differentially And Constitutively To Fgfr3mentioning
confidence: 83%
“…Alternatively, different mutations in the Lys650 residue could affect different intracellular localizations, which is now believed to have a role in chondrocyte defects observed in skeletal dysplasias (31). It should be noted that FGFR3 can be expressed as different isoforms, and while chondrocytes express the isoform IIIc, epithelial cells present the isoform IIIb.…”
Section: Discussionmentioning
confidence: 99%